An Analysis of Reward and Punishment in Enhancing Students’ Learning Motivation at SMPN 3 Bukit Sundi, Solok Regency - Nur Hayati; Rasidah Nasrah; Rahmi Fitri Yeni (The Future of Education Journal, 2026)
This study aims to identify and analyze the effect of reward and punishment on students’ learning motivation at SMPN 3 Bukit Sundi, Solok Regency. The background of this research is based on the relatively low level of students’ learning motivation, as indicated by suboptimal attendance rates, low active participation in learning activities, and the large number of students who fail to complete assignments on time. The implementation of reward and punishment at school has not been carried out consistently and optimally, thus requiring an empirical study regarding its influence on students’ learning motivation. This study employed a quantitative approach using a survey method. The results indicate that the provision of rewards does not have a positive and significant effect on students’ learning motivation. In contrast, punishment has a positive and significant effect on students’ learning motivation. Simultaneously, the implementation of reward and punishment has a positive and significant effect on students’ learning motivation at SMPN 3 Bukit Sundi, Solok Regency.